Catamenial Pneumothorax due to Suspected Thoracic Endometriosis Syndrome in a Woman with Adenomyosis and Cystoma Ovarii - Antariksa, Genta; Dwikarlina, Intan; Sutrisno, Sutrisno; Yudhanto, Hendy Setyo (Fakultas Kedokteran Universitas Brawijaya, 2025)
Catamenial pneumothorax (CP) is a recurrent spontaneous pneumothorax during the menstruation period and is often associated with thoracic-pelvic endometriosis. This case study reported a 39-year-old woman who presented with recurrent shortness of breath, particularly during menstruation. The patient also experienced severe dysmenorrhea and difficulty getting pregnant. Despite a negative sputum test, a history of chest tube insertion and tuberculosis treatment were identified. Elevated levels of the CA-125 marker were observed in a previous examination. Physical examination revealed decreased fremitus sounds on the mediobasal side, chest expansion, and right lung breath sounds. The plain radiograph displayed a visceral pleural line, air-fluid level appearance, and the collapse of the right hemithorax accompanied by fibrosis. The patient underwent inpatient treatment and had a chest tube inserted. A decortication thoracotomy procedure was performed, and anatomical pathology microscopic examination of the right lung tissue revealed a non-specific chronic inflammatory process accompanied by fibrosis.